Mulher e trabalho: significação e sentido no livro didático - Garcia, Ana Laura Gonçalves (Universidade Federal de São Carlos, 2024)
This research seeks to contribute to studies on the semantic analysis of textbooks, since these teaching materials are the main resources used for the training of students in Brazilian basic schools. In this sense, understanding the discourses present in the textbook on the most diverse subjects is an important way of identifying predominant trends in our society, as these are chosen to contribute to the formation of new generations. The most specific subject of this study is women in work relationships, understood here as work activity. Thus, we sought to understand the meanings, meanings and silencing of women in relation to work in statements extracted from textbook texts. The research is based on studies about the semantic analysis of the event, understood as defined by Eduardo Guimarães. The object of the research was obtained through the assessment of textbooks from public schools, which are among those approved by the Ministry of Education - MEC, in the National Textbook Program - PNLD. The object clipping was taken from Languages and its technologies textbooks approved by the PNLD, aimed at high school students and which address the theme of work. From this perspective, the study will address the meanings of women in the texts of teaching materials that deal with the topic of work, understood here as economic activity. In other words, we sought to identify how these statements signify women in texts produced for primary school students when the topic is work. In this way, the identification of the enunciative scene is necessary, as well as the social place of speech of the authors of the textbooks and the functioning of the statements taken from the text, having the text as an event as its premise. Thus, the analysis will enable the understanding of studies about the meaning and meaning of texts that refer to women in their relationship with work. It is concluded that despite female achievements in relation to gender asymmetries, in the texts analyzed, discursive memory is still guided by the vision of a passive, fragile, compliant and subservient woman to men. In these texts, work as a labor activity is, mainly, masculine, with the statements prevailing in silence about women and persistent inequalities, in relation to men, when the topic is the job market
Woman and work: meaning in textbooks
Keywords: Semântica do acontecimento; Sentidos; Mulher; Trabalho; Livro didático; Semantic of the event; Meanings; Woman; Work; Textbooks; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA